(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study attempts to show the impacts of agro tourism in environmental and climatic betterment of the state and nation. The results of this study will tell us that agro-tourism will help to improve environmental and climatic factors and also plays a great role as an additional income source for farmers and government. General public is now-a-day’s facing problem because of environmental instability and this can be cured if we consider agro tourism sector as a solution and incorporate this sector too like other tourism sector. Maharashtra was the first to understand this sectors demand and used this concept very well to improve its GDP and environment. Agro tourism help to create awareness among public about the environment by providing income source and environmental benefits both simultaneously. It creates knowledge about agriculture science. A modern style of development proposes rationalexploitation of agricultural resources together with the rediscovery of heritage both historical and naturalistic as a means to reach sustainable development. Agro tourism acts as the contact point between the tourist’s expectations of healthy environment, natural and fresh products, rediscovery of nature and best touristic services with an unforgettable experience. The study assumes the importance of environmental and climatic betterment to neutralize or reduce its harmful effects in near future. It helps to evaluate that how a sustainable development can be reached without causing damage to our environment. This synergy between agriculture and tourism capitalized on the combined benefits of development in agriculture as a primary sector and tourism as a service sector which further boost rural employment generation and environmental benefits. Thus, the paper suggests that agro-tourism has the potential for developing income opportunities and creates new ways for environmental and climatic betterment